Discover a world of knowledge and community-driven answers at IDNLearn.com today. Get accurate and detailed answers to your questions from our dedicated community members who are always ready to help.

Solve the rational equation. Express numbers as integers or simplified fractions.

[tex]\[ \frac{p}{7}-\frac{p}{p-9}=\frac{9}{9-p} \][/tex]

The solution set is [tex]$\square$[/tex].


Sagot :

To solve the rational equation

[tex]\[ \frac{p}{7} - \frac{p}{(p-9)} = \frac{9}{(9-p)}, \][/tex]

we follow these steps:

1. Identify the denominators: The denominators in the equation are [tex]\(7\)[/tex], [tex]\(p-9\)[/tex], and [tex]\(9-p\)[/tex].

2. Recognize the relationship between [tex]\(p-9\)[/tex] and [tex]\(9-p\)[/tex]:
[tex]\[ 9 - p = -(p - 9). \][/tex]

So, we can rewrite the right-hand side as:
[tex]\[ \frac{9}{(9-p)} = -\frac{9}{(p-9)}. \][/tex]

Therefore, our equation becomes:
[tex]\[ \frac{p}{7} - \frac{p}{(p-9)} = -\frac{9}{(p-9)}. \][/tex]

3. Combine the terms on the left-hand side by finding a common denominator:
The common denominator for [tex]\(7\)[/tex] and [tex]\(p-9\)[/tex] is [tex]\(7(p-9)\)[/tex]. Thus:
[tex]\[ \frac{p(p-9)}{7(p-9)} - \frac{7p}{7(p-9)} = -\frac{9 \times 7}{7(p-9)}. \][/tex]

Simplify and combine terms:
[tex]\[ \frac{p(p-9) - 7p}{7(p-9)} = \frac{-63}{7(p-9)}. \][/tex]

Combine the terms in the numerator:
[tex]\[ \frac{p^2 - 9p - 7p}{7(p-9)} = \frac{-63}{7(p-9)}, \][/tex]
which simplifies to:
[tex]\[ \frac{p^2 - 16p}{7(p-9)} = \frac{-63}{7(p-9)}. \][/tex]

4. Eliminate the denominators by multiplying both sides of the equation by [tex]\(7(p-9)\)[/tex]:
[tex]\[ p^2 - 16p = -63. \][/tex]

5. Form a quadratic equation:
[tex]\[ p^2 - 16p + 63 = 0. \][/tex]

6. Solve the quadratic equation: To solve [tex]\(p^2 - 16p + 63 = 0\)[/tex], we can use the quadratic formula, [tex]\(p = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 1\)[/tex], [tex]\(b = -16\)[/tex], and [tex]\(c = 63\)[/tex].

First, calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac = (-16)^2 - 4 \cdot 1 \cdot 63 = 256 - 252 = 4. \][/tex]

Then use the quadratic formula:
[tex]\[ p = \frac{16 \pm \sqrt{4}}{2 \cdot 1} = \frac{16 \pm 2}{2}. \][/tex]

This results in two solutions:
[tex]\[ p = \frac{16 + 2}{2} = 9 \quad \text{and} \quad p = \frac{16 - 2}{2} = 7. \][/tex]

7. Check the potential solutions for extraneous roots:

- For [tex]\(p = 9\)[/tex]:
Substitute [tex]\(p = 9\)[/tex] back into the original equation:
[tex]\[ \frac{9}{7} - \frac{9}{0} = \frac{9}{0}, \][/tex]
which is undefined due to division by zero. Hence, [tex]\(p = 9\)[/tex] is not a valid solution.

- For [tex]\(p = 7\)[/tex]:
Substitute [tex]\(p = 7\)[/tex] back into the original equation:
[tex]\[ \frac{7}{7} - \frac{7}{(7-9)} = \frac{9}{(9-7)}, \][/tex]
[tex]\[ 1 + \frac{7}{2} = \frac{9}{2}. \][/tex]
Simplifying both sides:
[tex]\[ 1 + \frac{7}{-2} = -3.5. \][/tex]
This correctly simplifies to [tex]\(4.5=4.5\)[/tex], making [tex]\(p = 7\)[/tex] a valid solution.

Thus, the solution set is [tex]\(\{7\}\)[/tex].